2018
DOI: 10.1186/s12885-018-4701-2
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant DNA methylation of ADAMTS16 in colorectal and other epithelial cancers

Abstract: BackgroundADAMs (a disintegrin and metalloproteinase) have long been associated with tumor progression. Recent findings indicate that members of the closely related ADAMTS (ADAMs with thrombospondin motifs) family are also critically involved in carcinogenesis. Gene silencing through DNA methylation at CpG loci around e.g. transcription start or enhancer sites is a major mechanism in cancer development. Here, we aimed at identifying genes of the ADAM and ADAMTS family showing altered DNA methylation in the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 32 publications
0
23
1
Order By: Relevance
“…PENK is down-regulated and methylated in prostate, bladder, pancreatic, and colorectal cancers 28 ; however, its relationship in GC has not been explored. The ADAMTS family is thought to play an important role in carcinogenesis; however, the function and regulation of ADAMTS16 in carcinogenesis are not clearly defined 29 .…”
Section: Discussionmentioning
confidence: 99%
“…PENK is down-regulated and methylated in prostate, bladder, pancreatic, and colorectal cancers 28 ; however, its relationship in GC has not been explored. The ADAMTS family is thought to play an important role in carcinogenesis; however, the function and regulation of ADAMTS16 in carcinogenesis are not clearly defined 29 .…”
Section: Discussionmentioning
confidence: 99%
“…STC2 was overexpressed in COAD, and its expression was positively correlated with the disease progression. Since many studies have shown that aberrant DNA methylation has a significant impact on gene expression and prognosis in some cancers[33,34], and a previous study reported that reducing the expression of DNA methyltransferase 1 could stimulate STC2 expression[35], we hypothesized that methylation might contribute to the overexpression of STC2. To verify this, the promoter DNA methylation data from TCGA Infinium HumanMethylation450K BeadChip arrays for COAD[36] were subjected to methylation analysis of the STC2 promoter.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have explored the impact of DNA methylation events on lung tumor initiation and progression 19 - 22 , 27 - 29 , 66 - 68 . However, those studies mainly investigated a single gene or a small number of genes and a NGS-based methylation investigation in lung cancer has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%